(untitled) (Research, Society and Development, 2022)
Attention Deficit/Hyperactivity Disorder (ADHD) begins in childhood and presents as symptoms of lack of attention, hyperactivity and difficulty in self-control. The objective was to identify the main studies and technological applications on ADHD and electroencephalogram (EEG) in databases and in patents. The research took place from September to December 2021, using the Web of Science and Pubmed databases for the survey of scientific articles and for patents: United States Patent and Trademark Office (USPTO), European Patent Office (EPO), World Intellectual Property Organization (WIPO) and the National Institute of Industrial Property (INPI) of Brazil. The results in the database showed the USA leading the ranking and the search for patents showed an increase in the number of filings. There is a need for greater investments in Brazilian technology, as the results showed few records in the INPI database, with greater attention being paid to the country’s technological development.